Overlooked risk of antibiotic resistance genes in typical landfill plumes and their influencing factors - Dongsheng Shen; Xin Gao; Cai Hui; Yuyang Long; Jiali Shentu; Li Lu; Shengqi Qi (Ecotoxicology and Environmental Safety, 2025)
Landfills are one of the primary reservoirs of antibiotic resistance genes (ARGs). Previous studies always focus on the distribution of ARGs in landfill leachate, while the distribution of ARGs in groundwater around the landfill and the corresponding influencing factors are always overlooked. In this study, seven groundwater samples and one leachate sample were collected from a typical landfill in Yueqing, China. Sulfonamide was the most abundant antibiotic in groundwater with its concentration of 1.2–23.1 ng L−1. Metagenomic analysis revealed 13 major types and 88 subtypes of antibiotic resistance genes (ARGs) in the leachate and surrounding groundwater. Multidrug (23.2–51.4 %), sulfonamide (2.6–24.1 %), tetracycline (3.0–35.8 %), macrolides-lincosamide-streptogramin (MLS, 1.1–26.3 %) and aminoglycoside (0.9–13.1 %) resistance genes were the top five types in the detected ARGs, while the ARGs abundance in groundwater increased with landfill age. Heavy metals (Ni, Pb, Cr, Cd) were strongly correlated with certain ARG subtypes, while no significant correlations were observed between antibiotics and their corresponding ARGs due to their low concentrations. Through co-occurrence network analysis, it was found that ARGs were tightly correlated with mobile genetic elements (MGEs), while several types of virulence factors such as flmH, cylG and clbF were also tightly correlated with MGEs. Besides, ARGs were also correlated with some denitrification genes such as nirB and norC, showing that the denitrification process would enhance the dissemination of ARGs. This study provides important insights for assessing the risk of ARGs spreading through leachate leakage in groundwater and can help optimize the management strategy of landfill.